Human motricity and health - Manuel Sérgio Vieira e Cunha (Journal of Physical Education (Maringá), 2008)
If human motricity science intends to study motor conduct (or actions) in which the human being pursues transcendence (or surmounting), it inevitably relates to the large realm of health. What are the aspects it evinces? Transdisciplinarity, solidarity among the various knowledge types (including poetical), complexity, (where the physical is integrated but surmounted) and the firm belief that to be healthy is to have in ourselves, alive and working, the capacity for surmounting anything.